Incorporating gender-inclusive language in undergraduate courses on anatomy and physiology of the speech mechanism - Smith, Julian; Smith, Keith; White, Evan (Perspectives of the ASHA Special Interest Groups, 2025)
Keywords: Competence (human resources); Cultural competence; Curriculum; English language; Language acquisition; Mechanism (biology); Multiculturalism; dept.cmd

The influence of side-lying position on oropharyngeal swallow function in at-risk infants: an exploratory study - Smith, Julian B.; Kamarunas, Erin; O’Donoghue, Cynthia (Clinical Pediatrics, 2023)
This investigation assessed the effect of side-lying position on infant oropharyngeal swallow physiology. Infant modified barium swallow studies (MBS) recordings were retrospectively examined in matched-pairs comparing at-risk infants swallowing in both an upright/cradled position and a side-lying position. Swallow parameters were measured independently and through a consensus coding approach. Infants fed in side-lying position showed a decrease in airway invasion severity as compared with when those same infants were fed in an upright/cradled position (P = .009). Bolus location at the time of swallow initiation was higher when infants were fed in side-lying position as compared with cradle position (P = .024), representing decreased risk of airway invasion. Infants fed in side-lying position demonstrated fewer swallows per breaths (P = .032). This pilot study validates the need for additional research to further define the mechanisms related to this improvement, and to determine how diagnosis and medical stability moderate these findings.
Keywords: dept.cmd; peer-reviewed

Speech-Language Pathologists' Use of Side-Lying Position in Infant Modified Barium Swallow Studies: A Qualitative Investigation - Smith, Julian Bergen; O, 'Donoghue Cynthia; Jones, Rebecca (Perspectives of the ASHA Special Interest Groups, 2024)
Purpose: This qualitative study explored the practices of hospital-based speech-language pathologists (SLPs) conducting modified barium swallow studies (MBS) for infants at risk for dysphagia. Specifically, this research aimed to determine whether or not SLPs use side-lying position during MBS, to examine possible differences in the use of positioning, and to better understand SLPs' perceptions and experiences in this practice. Using a constructivist view, research questions guiding this inquiry were as follows: What is the current practice of hospital-based pediatric SLPs in regard to the use of side-lying position during infant MBS? What is the experience of the hospital-based SLP in their use of side-lying position during MBS? How do SLPs report perceived barriers or benefits to using side-lying position during MBS? Method: Employing a purposive-convenience sampling technique, data were collected using semistructured interviews of SLPs serving at-risk infants with dysphagia. All participants were practicing in Level-III or -IV neonatal intensive care units. Interviews were recorded, transcribed, loaded into NVivo, and coded using initial and consensus coding. Themes achieved saturation following six interviews. Results: Three themes emerged from the analysis: (a) variations in practice patterns, (b) factors influencing clinical practice, and (c) items that SLPs identified as needs to facilitate change in their clinical practice. Conclusions: Although SLPs acknowledged the importance of MBS replicating an infant's typical feeding, some SLPs who consistently use side-lying position during feeding do not assess feeding in side-lying position during MBS. This inconsistency in practice results from SLPs' perceived barriers, including lack of experience, concern over interdisciplinary conflict, need for MBS protocols, and lack of research on the potential impacts of side-lying positioning on swallowing. Participants reported the need for research to determine whether side-lying position alters, possibly improves, swallow functions and safety (e.g., airway protection) for at-risk infants.
Keywords: dept.cmd; peer-reviewed

Dysphonia Outperforms Voice Change as a Clinical Predictor of Dysphagia - Griffin, Lindsay; Kamarunas, Erin; Smith, Julian Bergen; Kuo, Christina; O, 'Donoghue Cynthia (American Journal of Speech-Language Pathology, 2023)
Purpose: Changes in voice quality after consuming food or drink have been used as a clinical indicator of dysphagia during the clinical swallowing evaluation (CSE); however, there is conflicting evidence of its efficacy. This study investigated if dysphonia and/or voice change after swallowing are valid predictors of penetration, aspiration, or pharyngeal residue. Our approach aimed to improve current methodologies by collecting voice samples in the fluoroscopy suite, implementing rater training to improve interrater reliability and utilizing continuous measurement scales, allowing for regression analyses. Method: In this prospective study, 30 adults (aged 49–97 years) referred for a videofluoroscopic swallowing study (VFSS) were audio-recorded completing a sustained /i/ prior to VFSS and again after swallowing each bolus during the VFSS. Swallowing function was measured using the reorganized Penetration–Aspiration Scale and the Normalized Residue Ratio Scale. Following listener training, 84 voice samples were perceptually rated using the Consensus Auditory-Perceptual Evaluation of Voice (CAPE-V). Ordinal and logistic regression were used to determine whether voice quality and voice quality change after swallowing were predictors of airway invasion and pharyngeal clearance. Results: Results indicated that the presence of dysphonia at baseline during a sustained /i/ task as measured by the CAPE-V predicted airway invasion but not pharyngeal residue. Voice change after swallowing associated with vowel /i/ production as measured by the CAPE-V did not predict either dysphagia measure. Conclusion: These results indicate that voice change during a sustained /i/ after swallowing appears unrelated to airway invasion or pharyngeal residue; however, in the absence of known laryngeal pathology, dysphonia prior to a CSE should alert speech-language pathologists of a possible comorbid dysphagia.
Keywords: dept.cmd; peer-reviewed

Reliability of Lingual Swallow Pressure Measurements in Healthy Older and Younger Adults - Smith, Julian; Murray, Kelsey; Szynkiewicz, Sarah; Wasiuk, Peter; Dalton, M; Thompson, Kirsty; Kamarunas, Erin (Journal of Oral Rehabilitation, 2025)
Keywords: Bolus (digestion); Mastication; Measurement device; Reliability (semiconductor); Swallowing; dept.cmd; dysphagia; lingual strength; reliability; swallow pressureswallowingtongue strength